Furthering inclusive practices for students with an Autism Spectrum Disorder in Irish Primary Schools - McCann, Jennifer (Trinity College (Dublin, Ireland). School of Psychology, 2010)
Inclusion of students with autism spectrum disorder has been the focus of the research. Absent from previous research is the focus on how programmes written and designed for the U. S. school system can succeed in Ireland. The primary goal of the thesis is to supplement the work currently utilised in Ireland to educate students with autism spectrum disorder in the least restrictive environment. Specifically, the study presents a body of research to provide an understanding of inclusive practices for students with autism spectrum disorder in Irish primary schools. A mixed method approach was utilised to investigate the research questions posed. The first study, Chapter 2, presents a national survey which examined where and how students with autism spectrum disorder as well as other intellectual disabilities were being included in mainstream Irish primary schools.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin